Al-Qur’an dan Pengembangan Studi Agama (Telaah terhadap Yahudi, Kristen, Sabea, dan Majusi) - Qosim Nursheha Dzulhadi (Universitas Darussalam Gontor, 2014)
Al-Qur’an is known as an authentic source for comparative religion (‘ilm muqâranat al-adyân). There are six religions mentioned explicitly in the Qur’an in the verse (22: 17), namely: the believers, the Jews, the Christians, the Sabean, the Zoroastrians, and the idolater. This means that al-Qur’an is a holy book that pays great attention to comparative religion (muqâranat al-adyân). At this point, what al-Qur’an generally mentions is still a hot topic to discuss up to the present. In other words, what Al-Qur’an informs about these religions is always up to date and actual. Al-Quran criticized five major religions – except Islam – because those deviate from the true path of God. Such as Jews and Christians, for example considered to have far deviated from the true teachings of Tawheed. On this basis, these religious adherents have reached the degree of ‘infidels’ eventhough regarded as Ahl Kitab. Therefore, the other two religions Sabea (al-Sâbi’ûn) and Zoroastrian had turned away from Tawhid to be fire worshipers. Further, this paper will review the scholars’ criticism of these religions. Then asserted in this article that the only true religious path is Islam.